FRI0423 Effects of selexipag in cultured scleroderma skin fibroblasts. (12th June 2018) - Cutolo, M.; Ruaro, B.; Montagna, P.; Brizzolara, R.; Trombetta, A.C.; Scabini, S.; Tavilla, P.P.; Parodi, A.; Corallo, C.; Giordano, N.; Paolino, S.; Pizzorni, C.; et al.
Abstract : Background: In systemic sclerosis (SSc), the transition of fibroblasts into profibrotic myofibroblasts contributes to fibrosis through their over-production of extracellular matrix (ECM) proteins, primarily type I collagen (COL-1) and fibronectin (FN), a process which is mediated by the activation of fibrogenic intracellular signalling transduction molecules, including Erk1/2 and Akt kinases. 1, 2 Selexipag and its active metabolite (ACT-333679) are prostacyclin receptor agonists which leads to vasodilation in the pulmonary circulation and mainly used in the treatment of pulmonary arterial hypertension. Objectives: To investigate the possible effects of selexipag and ACT-333679 in downregulating the profibrotic activity of cultured SSc fibroblasts/myofibroblasts and the fibrogenic signalling molecules involved in the process. Methods: After obtaining Ethics Committee (EC) approval and informed consent, fibroblasts isolated from skin biopsies of 6 SSc patients (mean age 63±13 years) were cultured until the 3rd culture passage and then either maintained in normal growth medium (untreated cells) or independently treated with different concentrations of selexipag (from 30 µM to 0.3 µM) or ACT-333679 (from 10 µM to 0.1 µM) for 48 hours. Protein and gene expressions of α-smooth muscle actin (α-SMA), fibroblast specific protein-1 (S100A4), COL-1, and FN were investigated by Western blotting and qRT-PCR. Erk1/2 and Akt phosphorylation was investigated in untreated and ACT-333679 treated cells at 15 and 30 min as well as at 48 hours by Western botting. Results: Selexipag and ACT-333679 significantly reduced the protein synthesis and the gene expression of α-SMA, S100A4, and COL-1 in cultured SSc fibroblasts/myofibroblasts compared to untreated cells, primarily at the concentrations of 3 µM and 0.3 µM for selexipag and 1 µM and 0.1 µM for ACT-333679 (p<0.05). Differently, FN was significantly downregulated at protein level (p<0.05 vs. untreated cells). Of note, ACT-333679 significantly reduced the phosphorylation of Erk1/2 and Akt kinases already after 30 min of treatment in cultured SSc fibroblasts/myofibroblasts, and this effect was further maintained at 48 hours from treatment (p<0.05 vs. untreated cells, for all tested concentrations). Conclusions: For the first time selexipag and mainly its active metabolite ACT-333679 were found to interfere with the profibrotic activity of cultured SSc fibroblasts/myofibroblasts, possibly through the downregulation of fibrogenic Erk1/2 and Akt intracellular signalling molecules. References: [1] Ho YY, et al. Nature2014;10:390–402. [2] Distler JHW, et al. Arthrit Rheumatol2017;69:257–67. [3] Gatfield J, et al. J Pharmacol Exp Ther. 2017;362:186–99. Disclosure of Interest: M. Cutolo Grant/research support from: Actelion, Bristol-Mayer Squibb, Celgene, B. Ruaro: None declared, P. Montagna: None declared, R. Brizzolara: None declared, A. Trombetta: None declared, S. Scabini: None declared, P. P. Tavilla: None declared, A. Parodi: None declared, C. Corallo: None declared, N. Giordano: None declared, S. Paolino: None declared, C. Pizzorni: None declared, A. Sulli: None declared, V. Smith: None declared, S. Soldano: None declared